Clinicopathological features and prognostic outcomes of molecularly defined entities in the new edition of the WHO classification of sinonasal carcinoma - Vuong, Huy Gia; Le, Thoa; Le, Trang T.B.; Le, Hieu Trong; El-Rassi, Edward T.; McKinney, Kibwei A.; Dunn, Ian F. (Frontiers in Oncology, 2023)
Introduction: We investigated the clinicopathological features and prognoses of the new molecularly defined entities in latest edition of the World Health Organization (WHO) classification of sinonasal carcinoma (SNC) Methods: Integrated data were combined into an individual patient data (IPD) meta-analysis. Results: We included 61 studies with 278 SNCs including 25 IDH2-mutant, 41 NUT carcinoma, 187 SWI/SNF loss, and 25 triple negative SNCs (without IDH2 mutation, NUTM1 rearrangement, and SWI/SNF inactivation) for analyses. Compared to other molecular groups, NUT carcinoma was associated with a younger age at presentation and an inferior disease-specific survival. Among SNCs with SWI/SNF inactivation, SMARCB1-deficient tumors presented later in life and were associated with a higher rate of radiotherapy administration. SMARCA4-deficiency was mostly found in teratocarcinosarcoma while SMARCB1-deficient tumors were associated with undifferentiated carcinoma and non-keratinizing squamous cell carcinoma. Conclusion: Our study facilitates our current understanding of this developing molecular-defined spectrum of tumors and their prognoses.